2007
DOI: 10.1002/bem.20370
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to extremely low frequency magnetic fields affects insulin‐secreting cells

Abstract: To evaluate the effects of extremely low frequency magnetic field (ELFMF) on beta-cell survival and function, we cultured a hamster-derived insulin-secreting cell line (HIT-T15), which exhibits responsiveness to glucose in a semi-physiological range, under exposure to sham and ELFMF conditions, and assessed cell survival and function. We used our previously developed ELFMF exposure unit (a sinusoidal magnetic field at a frequency of 60 Hz, 5 mT) to culture cells under exposure to ELFMF conditions. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 23 publications
2
23
0
1
Order By: Relevance
“…Antihyperglycemic efficacy of PMF may imply that PMF treatment may prevent the destruction of pancreatic b-cells produced by STZ. Previous in vivo and in vitro studies have also shown that exposure to magnetic field caused an increase in serum insulin concentration and insulin secretion and led to reversible ultrastructural changes of pancreatic islets and an increase cell number [Laitl-Kobierska et al, 2002;Sakurai et al, 2008]. These findings have suggested that PMF could have a positive role in glycemic control and support our present investigation.…”
Section: Discussionsupporting
confidence: 91%
“…Antihyperglycemic efficacy of PMF may imply that PMF treatment may prevent the destruction of pancreatic b-cells produced by STZ. Previous in vivo and in vitro studies have also shown that exposure to magnetic field caused an increase in serum insulin concentration and insulin secretion and led to reversible ultrastructural changes of pancreatic islets and an increase cell number [Laitl-Kobierska et al, 2002;Sakurai et al, 2008]. These findings have suggested that PMF could have a positive role in glycemic control and support our present investigation.…”
Section: Discussionsupporting
confidence: 91%
“…Long-term exposure to an alternating MF at frequency 10 Hz, induction 8 mT and frequency 50 Hz, induction 20 AE 50 mT, led to a decrease in glucose concentration in the serum of experimental animals [Laitl-Kobierska et al, 2002;Sakurai et al, 2008]. This study showed that insulin treatment decreased the glucose levels in STZ-induced diabetic rats.…”
Section: Discussionmentioning
confidence: 52%
“…Earlier studies on the health influences of magnetic fields have not ensured clear answers with respect to a possible biological reaction (51). Some authors, however, have become increasingly persuaded that electrical and electromagnetic fields have effects on improvement of bones, tissue repair and other body regions (39,40,41). A few studies have shown positive effects of electromagnetic field on bone fractures, osteoporosis, and pseudoarthrosis (42).…”
Section: Resultsmentioning
confidence: 99%